Effect of Heating on the Pretreatment Process for Recycling Li-Ion Battery Cathode - Soraya Ulfa Muzayanha; Cornelius Satria Yudha; Luthfi Mufidatul Hasanah; Adrian Nur; Agus Purwanto (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
The use of Li-ion batteries has increased with the increasing of portable electronic media. Li-ion batteries have a life cycle hence a recycling process is needed in order to reduce the potential hazard of waste while increasing the economic value of unused battery material, especially its cathode active material. This study used Lithium Nickel Cobalt Oxide (NCA) cathode scrap to be regenerated which NCA material has high energy density and high capacity. The pretreatment process is one of the determinants in the subsequent recycling process. In this study, the effect of heating on the pretreatment process was carried out with variation temperatures of 500-8000C to obtain powder which will be recycled. The combination process of the leaching and co-precipitation was used to regenerate the cathode active material. Atomic Absorption Spectrophotometry (AAS) was performed to determine leaching efficiency using 4M H2SO4 at 400C for 3 hours. X-ray Diffraction (XRD) analysis showed that NCA material has been successfully regenerated which the diffraction peaks of NCA material was in accordance with JCPDS standards. The morphology of NCA material was tested using Scanning Electron Microscopy (SEM). Electrochemical testing uses a cylindrical battery at 2.7-4.2 Volt which the initial specific discharge capacity of the power is 62.13 mAh / g.